2017
DOI: 10.1590/1981-6723.15616
|View full text |Cite
|
Sign up to set email alerts
|

Extração e quantificação de carotenoides em minitomate desidratado (Sweet Grape) através da aplicação de diferentes solventes

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Extração e quantificação de carotenoides em minitomate desidratado (Sweet Grape) através da aplicação de diferentes solventes Extraction and quantification of carotenoids from dehydrated mini-tomatoes (Sweet Grape) by applying different solvents ResumoAtualmente, devido a eventos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…The carotenoids content was determined according to the literature [27,28]. The viability of the saponification execution was evaluated by reading after each stage: extraction, partition, and saponification.…”
Section: Determination Of Bioactive Compoundsmentioning
confidence: 99%
“…The carotenoids content was determined according to the literature [27,28]. The viability of the saponification execution was evaluated by reading after each stage: extraction, partition, and saponification.…”
Section: Determination Of Bioactive Compoundsmentioning
confidence: 99%
“…As it was previously stated, the carotenoid group includes the compounds lycopene and β ‐carotene; therefore, as seen in Figure 1, the approximation of these compounds can be perceived; thus demonstrating that the studied tomato varieties showcase a similar behavior when their quantification is observed. In a study by Nellis et al (2017), it was found that the amount of lycopene in tomatoes of the “Sweet Grape” variety corresponds to about 80% of total carotenoids in the sample, proving that it is the carotenoid pigment found in greater quantity in the fruit.…”
Section: Resultsmentioning
confidence: 97%
“…No que tange às extrações via soxhlet verifica-se que o melhor rendimento para obtenção do extrato foi obtido a partir do uso das cascas secas a 50 ºC. A presença de coloração forte nas amostras extraídas via soxhlet, conforme observa-se na Figura 3, indica a presença de outros compostos além daqueles também verificados no óleo essencial obtido via hidrodestilação, os quais estão sendo arrastados pelo solvente utilizado, dado que o hexano possui grande afinidade com substâncias orgânicas presentes em alimentos em geral, como o betacaroteno (Nellis et al, 2017).…”
Section: Obtenção Do óLeo Essencialunclassified